Process for preparation of Ziegler-Natta catalyst for polymerization of linear low density polyethylene
The described method for preparing a Ziegler-Natta catalyst by adding alkyl aluminum chloride and titanium to a magnesium chloride carrier addresses the complexity and impurity issues of existing methods, resulting in high-yield, high-elongation linear low-density polyethylene production.
Patent Information
- Application Number
- CN202380042193.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-05-27
- Filing Date
- 2023-05-10
- Publication Date
- 2025-01-03
AI Technical Summary
Existing Ziegler-Natta catalyst preparation methods are complex, sensitive to preparation conditions, and generate impurities, making them unsuitable for large-scale production of uniformly distributed polymers.
A method involving sequential addition of alkyl aluminum chloride and a titanium-containing metal compound to a magnesium chloride carrier with magnesium chloride alcoholate to prepare a Ziegler-Natta catalyst, allowing for controlled catalyst composition and improved polymerization of linear low-density polyethylene.
The method enables the production of linear low-density polyethylene with high yield, excellent copolymerization performance, and improved physical properties such as high elongation.
Smart Images

Figure CN119256024A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to a method for preparing a Ziegler-Natta catalyst for polymerization of linear low-density polyethylene, and a method for producing linear low-density polyethylene using the Ziegler-Natta catalyst prepared thereby. Background Art
[0002] Ziegler-Natta (Z / N) type polymerization catalysts are catalysts used to produce olefin polymers (e.g., ethylene copolymers). Typically, Ziegler-Natta catalysts contain a magnesium compound, an aluminum compound, and a titanium compound supported on a specific support.
[0003] Since the shape and size of polymers polymerized using Ziegler-Natta catalysts depend on the catalyst used, it is very important to prepare a catalyst that can increase productivity and produce uniformly distributed polymers.
[0004] Although a lot of development work has been done on the preparation of Ziegler-Natta catalysts, some methods are not suitable for large-scale preparation of catalysts due to significant sensitivity to preparation conditions or the generation of large amounts of impurities or waste. U.S. Patent No. 8,003,741 discloses a method for preparing a Ziegler-Natta catalyst, in which a magnesium compound is dissolved in an alcohol and then a titanium compound is added, but the preparation process is complex and the types of materials used are many. Summary of the invention
[0005] Technical issues
[0006] One embodiment of the present invention provides a method for preparing a Ziegler-Natta catalyst for polymerization of linear low density polyethylene.
[0007] Another embodiment of the present invention provides a Ziegler-Natta catalyst for polymerization of linear low-density polyethylene, which is prepared by the preparation method according to the above embodiment.
[0008] Still another embodiment of the present invention provides a method for producing linear low density polyethylene using the Ziegler-Natta catalyst for polymerization of linear low density polyethylene according to the above embodiment.
[0009] Technical solutions to technical problems
[0010] In a general aspect, a method for preparing a Ziegler-Natta catalyst for polymerization of linear low-density polyethylene comprises: sequentially adding an alkyl aluminum chloride represented by the following chemical formula 2 and a metal compound containing titanium (Ti) to a magnesium chloride carrier containing a magnesium chloride alcoholate represented by the following chemical formula 1 to allow a reaction to proceed;
[0011] [Chemical formula 1]
[0012] MgCl2·x(R 1 OH)
[0013] In Chemical Formula 1,
[0014] R 1 C 1-20 an organic group; and
[0015] x is 0.01 to 3.
[0016] [Chemical formula 2]
[0017] R 2 y AlCl 3-y
[0018] In chemical formula 2,
[0019] Each R 2 Independently for C 1-10 Alkyl or C 3-10 cycloalkyl; and
[0020] y is 1 to 2.
[0021] In another general aspect, provided is a Ziegler-Natta catalyst for polymerization of linear low-density polyethylene, the Ziegler-Natta catalyst being prepared by the method for preparing the Ziegler-Natta catalyst for polymerization of linear low-density polyethylene according to the above-mentioned embodiments.
[0022] In yet another general aspect, a method for producing linear low density polyethylene comprises contacting monomers containing ethylene with the Ziegler-Natta catalyst for the polymerization of linear low density polyethylene according to the above-described embodiments.
[0023] Advantageous Effects of the Invention
[0024] The present invention relates to a method for preparing a Ziegler-Natta catalyst for polymerization of linear low-density polyethylene (LLDPE), and specifically, the method for preparing a Ziegler-Natta catalyst for polymerization of linear low-density polyethylene according to one embodiment comprises: preparing a magnesium chloride carrier containing a magnesium chloride alcoholate obtained by mixing an excess of alcohol with magnesium chloride. In the method for preparing a Ziegler-Natta catalyst according to one embodiment, the catalyst composition can be easily controlled, thereby being able to effectively produce a linear low-density polyethylene having a variety of physical properties and excellent copolymerization performance. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] Figure 1 Graph showing XRD data for conventional α-phase MgCl2 (top) and magnesium chloride ethanolate prepared in Example 1.
[0026] Figure 2 : is a graph showing NMR data of magnesium chloride ethanolate prepared in Example 1.
[0027] 1 H NMR (500 MHz, THF-d8) ethanol δ 1.60 (t, J = 7.0 Hz, 3H), 3.70 (q, J = 7.0 Hz, 2H), 4.33 (s, 1H)
[0028] 1 H NMR (500 MHz, THF-d8) Toluene δ 12.33 (s, 3H), 7.16 (m, 5H)
[0029] [The CH3 peak of the internal standard is integrated at 2.331ppm, singlet = 3.00, the CH2 integration of -CH2- of ethanol at 1.160ppm, triplet = 3.911]
[0030] Figure 3 This figure shows the results of observing the magnesium chloride ethanolate prepared in Example 1 using a scanning electron microscope (SEM).
[0031] Figure 4 It is a graph showing the results of analyzing polymers produced using the Ziegler-Natta catalysts prepared in Examples and Comparative Examples by crystallization elution fractionation (CEF). DETAILED DESCRIPTION
[0032] The embodiments disclosed in this specification can be modified into various forms, and the technology according to the embodiments is not limited to the embodiments described below. In addition, throughout the specification, unless otherwise explicitly stated, "comprising" any component will be understood to mean including other components rather than excluding any other components.
[0033] The numerical range used in this specification includes upper and lower limits and all values within these upper and lower limits, increments derived from the form and span of the defined range logic, all double-limited values, and all possible combinations of upper and lower limits in numerical ranges defined in different forms. For example, when the content of the composition is limited to 10% to 80% or 20% to 50%, the numerical range of 10% to 50% or 50% to 80% should also be understood as recorded in this specification. Unless otherwise specifically defined in this specification, values that may appear outside the numerical range due to experimental errors or rounding of numerical values also fall within the defined numerical range.
[0034] Hereinafter, unless expressly defined otherwise in this specification, “about” may be considered to be a value within 30%, 25%, 20%, 15%, 10% or 5% of a stated value.
[0035] Hereinafter, "alkyl" in this specification is defined as being able to represent both alkyl and cycloalkyl. In addition, even if there is no specific definition, alkyl or cycloalkyl can also be interpreted as including derivatives that are expected to exert similar effects and that can be easily modified by those skilled in the art, or alkyl or cycloalkyl substituted with general substituents (e.g., halogen, etc.).
[0036] In the conventional method for preparing Ziegler-Natta catalyst, alcohol is added to magnesium chloride to form a support, wherein the magnesium chloride and alcohol are combined by reprecipitation, and an excess of titanium tetrachloride is used to remove the alcohol combined with the magnesium chloride. However, due to the use of excess titanium, it is difficult to prepare the catalyst, and the proportion of titanium loaded on the support becomes uneven with the reaction, which makes it difficult to reproduce the performance of the catalyst.
[0037] One embodiment provides a method for preparing a Ziegler-Natta catalyst for linear low-density polyethylene polymerization, wherein the Ziegler-Natta catalyst can achieve mild reaction conditions and minimal impurity generation. Through the preparation method according to the embodiment, a catalyst capable of supporting multiple transition metals on a carrier can be prepared, and the catalyst can be used to produce linear low-density polyethylene with high polymerization activity and excellent copolymerization performance.
[0038] One embodiment provides a method for preparing a Ziegler-Natta catalyst for polymerization of linear low-density polyethylene, the method comprising: sequentially adding an alkylaluminum chloride represented by the following Chemical Formula 2 and a metal compound containing titanium (Ti) to a magnesium chloride carrier containing a magnesium chloride alcoholate (complex) represented by the following Chemical Formula 1, so that the reaction proceeds:
[0039] [Chemical formula 1]
[0040] MgCl2·x(R 1 OH)
[0041] In Chemical Formula 1,
[0042] R 1 C 1-20 an organic group; and
[0043] x is 0.01 to 3.
[0044] [Chemical formula 2]
[0045] R 2 y AlCl 3-y
[0046] In chemical formula 2,
[0047] Each R 2 Independently for C 1-10 Alkyl or C 3-10 cycloalkyl; and
[0048] y is 1 to 2.
[0049] When the linear low density polyethylene is polymerized using the Ziegler-Natta catalyst prepared by the above-mentioned preparation method, the linear low density polyethylene can be produced with significantly increased yield and / or catalyst mileage. In addition, since the catalyst has excellent comonomer reactivity, compared to the commercially available linear low density polyethylene produced by conventional techniques, the linear low density polyethylene produced using the catalyst can have excellent physical properties such as high elongation because it has a high proportion of low density regions.
[0050] The magnesium chloride support according to one embodiment contains magnesium chloride alcoholate, which is an adduct of magnesium chloride and alcohol. In one embodiment, when an alcohol is used to prepare the magnesium chloride support, the magnesium chloride can be converted into magnesium chloride suitable for a support of a Ziegler-Natta catalyst. Alternatively, magnesium chloride induces lattice bonding on the surface of the support, thereby improving the performance of the catalyst. In addition, the magnesium chloride support according to one embodiment can be a spherical support.
[0051] According to one embodiment, the magnesium chloride alcoholate can be prepared by a method comprising: reacting MgCl2 with R 1 OH to obtain a magnesium chloride alcoholate solution; and
[0052] Solid magnesium chloride alcoholate is obtained by reducing the pressure of the magnesium chloride alcoholate solution.
[0053] In one embodiment, the solid magnesium chloride alcoholate can be obtained by filtering the precipitated solid (magnesium chloride alcoholate) by reducing the pressure of the magnesium chloride alcoholate solution, and then washing the filtered solid with a saturated hydrocarbon solution (such as pentane), and then the washed solid can be vacuum dried. In addition, the solid magnesium chloride alcoholate can also be obtained by heating the washed solid at a high temperature (about 70°C to 150°C, about 70°C to 130°C, about 80°C to 120°C, about 90°C to 110°C or about 110°C), and then the heated solid is vacuum dried under reduced pressure. The method for preparing magnesium chloride alcoholate according to one embodiment significantly solves the problems existing in the conventional reprecipitation method.
[0054] In one embodiment, MgCl2 (for example, anhydrous magnesium chloride) and R 1 OH (for example, anhydrous ethanol) is mixed, preferably an excess amount of R 1 For example, the molar ratio of magnesium chloride to alcohol in the mixing step can be 1:5 to 1:20, 1:5 to 1:15, 1:5 to 1:12, 1:6 to 1:10, 1:7 to 1:10, or about 1:8.
[0055] The preparation method according to one embodiment may further include: after adding the metal compound to allow the reaction to proceed, additionally adding an alkylaluminum chloride represented by Chemical Formula 2 (support activation step).
[0056] In one embodiment, the metal compound may further contain a transition metal, for example, a metal of Group IV or Group V. Specifically, the metal compound may further contain one or more metals selected from the group consisting of Zr, Hf, V, Nb, and Ta. In this case, the metal may exist in the form of chloride, alkoxy chloride, alkylate, etc. However, this is only an example, and the metal is not limited thereto.
[0057] In one embodiment, the metal compound containing titanium (Ti) may contain TiX4 or (R 3 O) z Ti(X) 4-z In this case, X is a halogen atom such as I, Br, Cl or F, and each R 3 are independently linear or branched C 1-10 Alkyl, C 1-8 Alkyl, C 2-6 Alkyl or C 1-5 alkyl, z is an integer from 1 to 4. Specific examples of the metal compound include TiCl4, TiBr4, TiI4, tetrabutyl titanate (Ti(OBu)4), tetraisopropyl titanate (Ti(Oi-Pr)4), tetraethyl titanate (Ti(OEt)4), diethoxytitanium dichloride (Ti(OEt)2(Cl)2) and monoethoxytitanium trichloride (Ti(OEt)(Cl)3). However, this is only an example, and the metal compound is not limited thereto.
[0058] In one embodiment, the metal compound containing titanium (Ti) may be a mixed metal compound further comprising a Group V metal compound. For example, the metal compound according to one embodiment may be a mixed metal compound of a metal compound containing titanium (TiCl4) and a Group V metal compound containing a Group V metal (VOCl3).
[0059] In one embodiment, R 1 It may be, for example, methyl, ethyl, n-propyl, isopropyl, n-butyl, isobutyl, n-pentyl, isopentyl, neopentyl, cyclopentyl, n-hexyl, n-heptyl, n-octyl, decyl, dodecyl, 2-methylpentyl, 2-ethylbutyl, 2-ethylhexyl, cyclohexyl, methylcyclohexyl, benzyl, methylbenzyl or isopropylbenzyl, but this is only an example, and R 1In one embodiment, the alcohol may be methanol, ethanol, n-propanol, isopropanol, n-butanol, isobutanol, n-pentanol, isopentanol, neopentyl alcohol, cyclopentanol, n-hexanol, n-heptanol, n-octanol, decanol, dodecanol, 2-methylpentanol, 2-ethylbutanol, 2-ethylhexanol, cyclohexanol, methylcyclohexanol, benzyl alcohol, methylbenzyl alcohol or isopropylbenzyl alcohol, but this is just an example, and the alcohol is not limited to this.
[0060] In one embodiment, x may be 5.0 or less, 4.0 or less, 3.0 or less, 0.5 to 5.0, 0.5 to 4.0, 0.5 to 3.0, 0.5 to 2.0, 0.8 to 2.0, or about 0.92 to 1.62, but is not limited thereto.
[0061] In one embodiment, R 2’ Each of them can be a straight chain or branched chain C 1-6 Alkyl, C 1-5 Alkyl, C 2-5 Alkyl, -CH3, -CH2CH3, -CH2CH2CH3, -CH2CH2CH2CH3, C 3-6 Cycloalkyl, C 4-6 Cycloalkyl or C 5-6 Cycloalkyl, but this is just an example, R 2 It is not limited to this.
[0062] In one embodiment, y can be, for example, 0, 1 / 2, 1, 3 / 2, or 2.
[0063] In one embodiment, the alkylaluminum chloride represented by Chemical Formula 2 may be ethylaluminum sesquichloride (C6H 15 Al2Cl3, also known as (C2H5) 3 / 2 AlCl 3 / 2 ), ethylaluminum dichloride (EtAlCl2), methylaluminum dichloride (MeAlCl2), propylaluminum dichloride (PrAlCl2) or butylaluminum dichloride (BuAlCl2), one or more alkylaluminum chlorides can be used simultaneously or in combination. In one embodiment, the alkylaluminum chloride can be a monomer or a dimer.
[0064] In one embodiment, the amount of the alkylaluminum chloride represented by Chemical Formula 2 is 10 equivalents or more relative to the molar number of the metal compound, so that a catalyst with more excellent activity can be prepared. For example, the molar ratio of the metal compound to the alkylaluminum chloride represented by Chemical Formula 2 can be 1:10 to 1:50, 1:15 to 1:45, 1:20 to 1:40, 1:25 to 1:35, 1:28 to 1:32 or about 1:30. However, this is just an example, and the molar ratio is not limited thereto.
[0065] In one embodiment, the molar ratio of the metal compound to the magnesium chloride support can be 1:0.1 to 1:30, 1:1 to 1:30, 1:5 to 1:30, 1:8 to 1:30, 1:10 to 1:30, 1:5 to 1:20, 1:10 to 1:20, 1:12 to 1:18, or about 1:15. However, this is just an example, and the molar ratio is not limited thereto.
[0066] In one embodiment, the magnesium chloride support may have a peak at the following diffraction angle 2θ in an X-ray diffraction pattern:
[0067] 7°±2.0° to 10°±2.0°, 31°±2.0° and 33°±2.0°
[0068] The magnesium chloride alcoholate according to one embodiment may have a broad peak within a peak range. For example, peaks at about 7.5° and 7.9° may overlap each other. The value of the diffraction angle may include an error value within a range of about ±0.2°.
[0069] In one embodiment, adding the alkylaluminum chloride to the magnesium chloride support may include the steps of diluting the obtained high-purity support in a saturated hydrocarbon (e.g., heptane) solution to prepare a slurry, and then adding the alkylaluminum chloride diluted in the saturated hydrocarbon (e.g., hexane) solution at room temperature (e.g., about 5°C to 25°C, about 10°C to 25°C, about 15°C to 25°C, or about 18°C to 23°C).
[0070] In one embodiment, the magnesium chloride support may have a particle size of about 5 to 80 μm, 10 to 80 μm, 20 to 60 μm, 10 to 50 μm, 20 to 40 μm, or about 40 μm (± 20%) when measured based on SEM analysis.
[0071] Another embodiment provides a Ziegler-Natta catalyst for polymerization of linear low-density polyethylene, which is prepared by the method for preparing the Ziegler-Natta catalyst for polymerization of linear low-density polyethylene according to the embodiment.
[0072] Another embodiment provides a method for producing linear low density polyethylene using the Ziegler-Natta catalyst for the polymerization of linear low density polyethylene according to the embodiment. Specifically, the method for producing linear low density polyethylene includes contacting the olefin monomer containing ethylene with the Ziegler-Natta catalyst for the polymerization of linear low density polyethylene according to the embodiment. In one embodiment, the olefin monomer can also include, for example, an olefin monomer with 2 to 20, 2 to 15 or 4 to 10 carbon atoms. For example, the olefin monomer can be propylene, butene, pentene, hexene, heptene, octene, nonene or decene, specifically, can be 1-propylene, 1-butene, 1-pentene, 1-hexene, 1-heptene, 1-octene, 1-nonene or 1-decene. However, this is just an example, and the olefin monomer is not limited to the above-mentioned olefin.
[0073] In one embodiment, the density of the linear low density polyethylene may be 0.91 g / mL to 0.94 g / mL, 0.912 g / mL to 0.938 g / mL, 0.915 g / mL to 0.935 g / mL, or 0.915 g / mL to 0.924 g / mL, but this is just an example and the density of the linear low density polyethylene is not limited thereto. In one embodiment, the melt index (MI) of the linear low density polyethylene can be 1.0 g / 10 min to 5.0 g / 10 min, 1.0 g / 10 min to 4.0 g / 10 min, 1.0 g / 10 min to 3.5 g / 10 min, 1.0 g / 10 min to 3.0 g / 10 min, 1.0 g / 10 min to 2.5 g / 10 min, 1.5 g / 10 min to 2.5 g / 10 min, or 1.6 g / 10 min to 2.3 g / 10 when measured at about 190° C. according to ISO 1133:1997 or ASTM D1238:1999, but this is just an example and the melt index of the linear low density polyethylene is not limited thereto. DETAILED DESCRIPTION
[0074] Hereinafter, the embodiments and experimental examples will be described in detail. However, the embodiments and experimental examples to be described below only illustrate a part of the embodiment, and the technology described in this specification is not limited thereto.
[0075] <Example 1>
[0076] Into a 500mL Schlenk flask, 20g (0.21mol) of anhydrous magnesium chloride and 250mL of heptane were injected. Then stirred. Stirring was performed to prevent agglomeration, the internal temperature of the reactor was raised to a temperature of about 70°C to 80°C, and then 77g (1.70mol) of anhydrous ethanol was slowly added dropwise and stirred to prevent agglomeration, thereby preparing a transparent dissolved magnesium chloride solution. After the magnesium chloride was dissolved, the pressure was slowly reduced to remove the ethanol in the flask. As the ethanol was removed, magnesium chloride ethanolate began to precipitate. An amount of ethanol similar to the initial amount was removed, and then the precipitated magnesium chloride was filtered, washed with 100mL of pentane twice or more, and vacuum dried to recover the magnesium chloride ethanolate. In order to remove the ethanol residue of the vacuum-dried magnesium chloride ethanolate, the magnesium chloride ethanolate was heated to 100°C and vacuum dried under reduced pressure to obtain a white powdery magnesium chloride ethanolate carrier (MgCl2·n(EtOH)).
[0077] The magnesium chloride ethanolate carrier of 190mg (2.00mmol) is transferred in a transparent vial, 10mL of heptane is added, and it is fully stirred to disperse.Afterwards, 0.54mL (0.53mmol) of 1.0M C2H5AlCl2 hexane solution diluted in hexane is injected, and it is stirred at room temperature for more than 6 hours.Afterwards, 1.1mL (0.14mmol) of 5 % by weight TiCl4 is slowly dripped, and it is stirred for more than 12 hours.In addition, 3.5mL (3.50mol) of 1.0M C2H5AlCl2 hexane solution is slowly dripped, and it is stirred for more than 12 hours, thereby preparing the catalyst (Ziegler-Natta catalyst) heptane slurry solution of the magnesium chloride load of pink.
[0078] <Example 2 and Example 3>
[0079] A magnesium chloride-supported catalyst (Ziegler-Natta catalyst) heptane slurry solution was prepared in the same manner as in Example 1, except that the metal compound shown in Table 1 was used.
[0080] <Comparative Example 1>
[0081] Into a 500 mL flask, 33 mL (30.0 mmol) of a 0.9 M ethyl normal butylmagnesium heptane solution was injected, followed by 127 mL of normal heptane. The internal temperature of the reactor was lowered to 0°C, and then hydrogen chloride (HCl) gas was added and stirred using a magnetic stirrer. Anhydrous hydrogen chloride gas was injected at a constant rate until no residual alkyl magnesium Grignard was observed, and the reaction was terminated to prepare a 0.2 M magnesium chloride carrier heptane slurry solution.
[0082] Afterwards, 10 mL (2.00 mmol) of the prepared 0.2 M magnesium chloride carrier solution was transferred to a transparent vial, 0.52 mL (0.52 mmol) of a 1.0 M C2H5AlCl2 solution diluted in hexane was injected as an alkylaluminum chloride, and stirred at room temperature for more than 6 hours. Afterwards, 1.0 mL (0.13 mmol) of 5 wt % TiCl4 was slowly added dropwise, and stirred for more than 12 hours, thereby preparing a brown magnesium chloride supported catalyst (Ziegler-Natta catalyst) heptane slurry solution.
[0083] <Comparative Example 2>
[0084] The process was carried out in the same manner as in Comparative Example 1 except that the alkylaluminum chloride shown in Table 1 was used. As a result, no catalyst was obtained.
[0085] [Table 1]
[0086]
[0087] 1) Alkyl aluminum chloride A: Ethyl aluminum dichloride (C2H5AlCl2) 2) Metal compounds
[0088] B: TiCl4; C: Ti(Oi-Pr)4; D: TiCl4 + VOCl3 (molar ratio = 1:1)
[0089] <Experimental Example 1> X-ray Diffraction (XRD) Analysis
[0090] XRD analysis was performed under the following equipment and analysis conditions to obtain the XRD spectrum of the magnesium chloride ethanolate support prepared in Example 1 ( Figure 1 ).
[0091] Manufacturer: Empyrean; X-ray source anode: Cu; generator voltage: 45 kV, tube current: 40 mA; incident beam: BBHD; divergence slit: 1 / 4°; anti-scatter slit: 1°; detector: PIXcel detector; sample stage: reflection-transmission rotator
[0092] Figure 1 XRD spectra of conventional α-phase MgCl and magnesium chloride ethanolate (MgCl2·n(EtOH), n=0.92 to 1.62) prepared in Example 1 are shown. In the case of magnesium chloride ethanolate (MgCl2·n(EtOH), n=0.92 to 1.62) prepared in Example 1, a broad peak can be confirmed near a diffraction angle (2θ) of about 7° to 10° (peaks at 7.5° and 7.9° overlap each other).
[0093] <Experimental Example 2> Nuclear Magnetic Resonance (NMR) Analysis
[0094] NMR analysis was performed under the following equipment and analysis conditions to obtain the XRD spectrum of the magnesium chloride ethanolate support prepared in Example 1.
[0095] Instrument manufacturer: Bruker; Power Hz: 500 MHz; NMR solvent: THF-d8
[0096] First, toluene and the magnesium chloride ethanolate prepared in Example 1 were stirred and completely dissolved in THF-d8 as an NMR analysis solvent, and then measured. 1 HNMR Figure 2 ). Then, the molar ratio of toluene to ethanol was calculated and the final weight of ethanol was estimated. The result was that the molar ratio of magnesium chloride to ethanol in the magnesium chloride ethanolate was 1:0.92 to 1:0.62.
[0097] <Experimental Example 3> Scanning Electron Microscope (SEM) Analysis
[0098] The magnesium chloride ethanolate prepared in Example 1 was subjected to SEM analysis under the following conditions. The results are shown in FIG. Figure 3 shown.
[0099] Manufacturer: Hitachi, Model: SU8230, Mode: SE, Detector: SE, Acceleration voltage: 5 kV, Current: 10 μA
[0100] As a result of measuring the particle size of magnesium chloride ethanolate based on the SEM results, it was confirmed that particles having a particle size of about 40 μm±20% were mainly generated.
[0101] <Experimental Example 4> Polymerization of Linear Low-Density Polyethylene
[0102] Under a stable anhydrous nitrogen atmosphere, 0.5 L of a saturated hydrocarbon solvent (methylcyclohexane) was charged into an autoclave reactor, 0.2 g (0.15 mol) of triethylaluminum and 100 mL (70 g, 0.7 mol) of 1-octene were injected, the reactor temperature was raised to 180° C., stirring was performed, and then ethylene was injected into the reactor at 30 bar. The catalysts (1.7 μmol) prepared in Examples 1 to 3 and Comparative Example 1 were diluted with a saturated hydrocarbon solvent (methylcyclohexane) (3 mL), and each catalyst was transferred to a catalyst port, and the catalyst port was pressurized with anhydrous nitrogen (50 bar). After the inside of the autoclave reactor was saturated with ethylene, the catalyst was injected into the reactor from the catalyst port under an isothermal condition of 180° C., and semi-batch polymerization was performed for 10 minutes under continuous supply of ethylene. Thereafter, the reactant was recovered through an outlet, and the solvent was dried to obtain a linear low-density copolymer (linear low-density polyethylene (LLDPE)). The yield, catalyst productivity, melt index and density of the obtained linear low density polyethylene were measured. The results are shown in Table 2.
[0103] At this time, catalyst mileage is defined as a value obtained by dividing the mass of produced LLDPE by the mass of the catalyst. The melt index was measured by testing at 190° C. according to ASTM D1238 standard, and the density was measured using a density gradient column.
[0104] [Table 2]
[0105]
[0106] Referring to Table 2, it can be seen that, compared with the case where the polymerization was carried out using the catalyst for linear low-density polyethylene polymerization prepared in the comparative example, the yield of the copolymer was significantly increased when the polymerization was carried out using the catalyst prepared in the example.
[0107] <Experimental Example 5> Crystallization Elution Fractionation (CEF)
[0108] In order to analyze the physical properties of the polymers prepared using the catalysts of the examples and comparative examples by crystallization elution fractionation (CEF), a POLYMER-CHARCRYTEX-42 instrument and a trichlorobenzene (TCB) solution were used for testing. At this time, commercial product A (Dow Chemical Company) and commercial product B (SK Chemicals Co., Ltd.) were prepared and tested as a comparison group. The results are shown in FIG. Figure 3shown.
[0109] Through the above experiments, it can be confirmed that in the case of the polymer prepared using the catalyst of the example, compared with the commercially available product, in the CEF spectrum, the proportion of the high-density region (homopolymer) at about 80° C. to 100° C. is low, and the proportion of the low-density region (copolymer) at about 50° C. to 80° C. is high. Therefore, it can be seen that the catalyst of the example can effectively prepare a low-density copolymer with high elongation.
[0110] Above, an embodiment is described in detail through preferred embodiments and experimental examples, but the scope of the embodiment is not limited to the specific embodiment, but should be interpreted according to the appended claims.
Claims
1. A method for preparing a Ziegler-Natta catalyst for the polymerization of linear low density polyethylene, comprising: Alkyl aluminum chloride represented by the following Chemical Formula 2 and a metal compound containing titanium (Ti) are sequentially added to a magnesium chloride carrier containing a magnesium chloride alcoholate represented by the following Chemical Formula 1 to allow the reaction to proceed: [Chemical formula 1] MgCl2·x(R 1 OH) In Chemical Formula 1, R 1 C 1-20 an organic group; and x is 0.01 to 3, [Chemical formula 2] R 2 y AlCl 3-y In chemical formula 2, Each R 2 Independently for C 1-10 Alkyl or C 3-10 cycloalkyl; and y is 1 to 2.
2. The method according to claim 1, wherein the magnesium chloride alcoholate represented by Chemical Formula 1 is prepared by a method comprising: By mixing MgCl2 with R 1 OH to obtain a magnesium chloride alcoholate solution; and Solid magnesium chloride alcoholate is obtained by reducing the pressure of the magnesium chloride alcoholate solution. 3 . The method according to claim 1 , further comprising, after adding the metal compound to allow the reaction to proceed, additionally adding an alkylaluminum chloride represented by Chemical Formula 2. 4 .
4. The method according to claim 1, wherein the metal compound further contains a Group IV or Group V metal. The method according to claim 1 , wherein x is from 0.5 to 2.
0.
6. The method according to claim 1, wherein each R 2 Independently for C 1-6 Alkyl or C 3-6 cycloalkyl, and y is 1 to 2. 7 . The method according to claim 1 , wherein the metal compound and the alkylaluminum chloride represented by Chemical Formula 2 are added in a molar ratio of 1:10 to 1:
50.
8. The method according to claim 1, wherein the metal compound and the magnesium chloride support react with each other in a molar ratio of 1:0.1 to 1:
30.
9. The method according to claim 1, wherein the metal compound contains TiX4 or (R 3 O) z Ti(X) 4-z , where X is a halogen atom, each R 3 Independently for C 1-10 The alkyl group, z is an integer from 1 to 4.
10. The method of claim 9, wherein the metal compound is a mixed metal compound further comprising a compound containing a Group V metal.
11. The method according to claim 1, wherein the alkylaluminum chloride is ethylaluminum dichloride (EtAlCl2), methylaluminum dichloride (MeAlCl2), propylaluminum dichloride (PrAlCl2), butylaluminum dichloride (BuAlCl2) or (C2H5) 3 / 2 AlCl 3 / 2 . 12 . A Ziegler-Natta catalyst for the polymerization of linear low-density polyethylene, prepared by the method for preparing a Ziegler-Natta catalyst for the polymerization of linear low-density polyethylene according to claim 1 .
13. A process for producing linear low density polyethylene, comprising contacting ethylene with the Ziegler-Natta catalyst for the polymerization of linear low density polyethylene as claimed in claim 12.
14. The method according to claim 13, wherein: The linear low density polyethylene has a density of 0.91 g / mL to 0.94 mL, and a melt index (MI) of 1.0 g / 10 min to 5.0 g / 10 min when measured according to ASTM D1238.